The Effect of Education, Health, and Inflation to Poverty in West Java Province - Chairunnisha, Mutiara; Saptono, Ari; Nikensari, Sri Indah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The United Nations focusing on Poverty as the problem that considered still difficult to solve. Through the Sustainable Development Goals (SDGs), the problem of poverty is a top priority that must be ended by 2030. West Java Province as the Heart of National Industry has many superior resources compared to other provinces. However, West Java Provinces is still the province with the second highest number of poor people nationally. The aim of this study is to measure an econometric estimation to measure the role of education, health, and inflation on poverty in West Java Province. The model used in this research is panel data from 7 districts/cities in West Java Province from 2011-2022, using multiple linear regression analysis with quantitative methods. Education has a negative influence on poverty, health has a negative influence on poverty, and inflation does not have a positive influence on poverty. This study shows that poverty in West Java Province is influenced by education and health, where if the average level of years of schooling and the health index increases, the poverty level will decrease. On the other hand, inflation has no influence on the poverty level in West Java Province.